Effects of Mild and Moderate Monoclonal Antibody Dose on Inflammation, Bone Loss, and Activation of the Central Nervous System in a Female Collagen Antibody-induced Arthritis Mouse Model. (August 2021) - Williams, Bonnie; Lees, Florence; Tsangari, Helen; Hutchinson, Mark R.; Perilli, Egon; Crotti, Tania N.
Induction of severe inflammatory arthritis in the collagen antibody-induced arthritis (CAIA) murine model causes extensive joint damage and pain-like behavior compromising analysis. While mild models are less severe, their reduced, variable penetrance makes assessment of treatment efficacy difficult. This study aimed to compare macroscopic and microscopic changes in the paws, along with central nervous system activation between a mild and moderate CAIA model. Balb/c mice ( n =18) were allocated to control, mild, and moderate CAIA groups. Paw inflammation, bone volume (BV), and paw volume (PV) were assessed. Histologically, the front paws were assessed for joint inflammation, cartilage damage, and pre/osteoclast-like cells and the lumbar spinal cord and the periaqueductal gray (PAG) region of the brain for glial reactivity. A moderate CAIA dose induced (1) significantly greater local paw inflammation, inflammatory cell infiltration, and PV; (2) significantly more osteoclast-like cells on the bone surface and within the surrounding soft tissue; and (3) significantly greater glial reactivity within the PAG compared with the mild CAIA model. These findings support the use of a moderate CAIA model (higher dose of monoclonal antibodies with low-dose lipopolysaccharide) to induce more consistent histopathological features, without excessive joint destruction.